¿Por qué no hay onicóforos en Cuba? - Monge, Julián (Universidad de Costa Rica, 2019)
I propose here that there are no onychophorans in Cuba because the predominant marine currents - which could bring onychophorans from the Southern lands - mainly reach Jamaica and Hispaniola (island that contains Haiti and the Dominican Republic). I present five new predictions about the dispersal history of Caribbean species that, hopefully, will inspire new generations of geneticists to test them.